A Mouse Model of Delayed Rotator Cuff Repair Results in Persistent Muscle Atrophy and Fatty Infiltration. Issue 12 (October 2018) - Wang, Zili; Liu, Xuhui; Davies, Michael R.; Horne, Devante; Kim, Hubert; Feeley, Brian T.
Background: Rotator cuff (RC) tears are common tendon injuries seen in orthopaedic patients. Successful repair of large and massive RC tears remains a challenge due to our limited understanding of the pathophysiological features of this injury. Clinically relevant small animal models that can be used to study the pathophysiological response to repair are limited by the lack of chronic repair models. Purpose: To develop a highly clinically relevant mouse model of delayed RC repair. Study Design: Controlled laboratory study. Methods: Three-month-old C57BL/6J mice underwent unilateral supraspinatus (SS) and infraspinatus (IS) tendon tear with immediate, 2-week delayed, or 6-week delayed tendon repair. Animals with no repair or sham surgery served as controls. Gait analysis was conducted to measure shoulder function at 2 weeks and 6 weeks after surgery. Animals were sacrificed 6 weeks after the last surgery. Shoulder joint, SS, and IS muscles were harvested and analyzed histologically. Ex vivo mechanical testing of intact and repaired SS and IS tendons was conducted. Reverse-transcriptase polymerase chain reaction was performed on SS and IS muscles to quantify atrophy, fibrosis, and fatty infiltration–related gene expression. Results: Histological and tendon mechanical testing showed that torn tendons could be successfully repaired as late as 6 weeks after transection. However, significant atrophy and fatty infiltration of muscle, with impaired shoulder function, were persistent in the 6-week delayed repair group. Shoulder function correlated with the severity of RC muscle weight loss and fatty infiltration. Conclusion: We successfully developed a clinically relevant mouse model of delayed RC repair. Six-week delayed RC repair resulted in persistent muscle atrophy and fatty infiltration with inferior shoulder function compared with acute repair. Clinical Relevance: Our novel mouse model could serve as a powerful tool to understand the pathophysiological and cellular/molecular mechanisms of RC muscle and tendon degeneration, eventually improving our strategies for treating and repairing RC tears.